Umayyads and ʻAbbásids, being the fourth part of Jurjí Zaydán's history of Islamic civilization - Zaydān, Jirjī, 1861-1914 (Kitab Bhavan, 1978)
History of the Islamic Empire during the reigns of the Omayyad and Abbasid dynasties.